Mandatory Pain Assessment in a Pediatric Emergency Department: Failure or Success?. Issue 10 (October 2019) - Marzona, Federico; Pedicini, Sara; Passone, Eva; Pusiol, Anna; Cogo, Paola
Abstract : Objective: Pain control is a priority in patient evaluation. Despite the proliferation of guidelines, pain is still underassessed and undertreated, especially in children. To improve efficiency and to adhere to best medical practice, our triage software was upgraded; it included mandatory pain scoring for the admission of a child to the pediatric emergency service, thereby limiting the chances of overlooking a child experiencing pain. We conducted this study to verify the effect of routine versus mandatory pain scoring on pain management under the hypothesis that mandatory pain assessment would improve reevaluation and pain treatment. Methods: This retrospective case-control study was conducted in our Pediatric Emergency Department (ED). We collected data with regard to pain assessment and reassessment at triage and during the entire stay in the ED, and also with regard to the drugs eventually administered. We reviewed the charts of 1274 patients admitted with the older triage software and those of 1262 patients admitted with the newer triage software (intervention group). Results: Pain was evaluated significantly more frequently in the intervention group at triage, during the medical evaluation, and at discharge. In the intervention group, a smaller percentage of patients were treated for pain at both triage and during their stay in the ED ( P =0.078 and 0.048). Pain reassessment resulted lower in the intervention group ( P <0.01). Discussion: Mandatory pain assessment improved the pain evaluation rate. This did not, however, translate into better treatment and management of pain in the pediatric emergency setting.